SOBRE LA ESTRUCTURA DE LA GLANDULA PINEAL I ARMAZON NEUROGLICO - VON LICHTENBERG, F; COSTERO, ISSAC CARLOS (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1943)
The results obtained following electrical stimulation of various parts of the brain are reviewed with reference to the epileptic crisis It is con-cluded that wherever the origin of the convulsive crisis, different functional levels of the brain rapidly e
BOL INST ESTUD MED BIOL
Keywords: ESTRUCTURA, GLANDULA, ARMAZON, NEUROGLICO; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA